TERRORISM AS A THREAT TO BORDER SECURITY - Hafiz Musayev (International Journal of Innovative Technologies in Social Science, 2023)
The article gives a general description of terrorism. Including the development trends of terrorism in the modern era. The article mainly examines terrorism as a threat to border security. Attention is paid to the close links between terrorism and the drug trade as a threat to border security. The characteristics of the activities of terrorist organizations are also touched upon, and the activity of Armenia as a state that implements and supports terrorism is investigated. Opinions of researchers in this field are reported. At the end, appropriate conclusions are drawn.